Comparative effectiveness of neoadjuvant chemotherapy in bladder and upper urinary tract urothelial carcinoma - D'Andrea, David; Matin, Surena; Black, Peter C; Petros, Firas G; Zargar, Homayoun; Dinney, Colin P; Cookson, Michael S; Kassouf, Wassim; Dall'Era, Marc A; McGrath, John S; Wright, Jonathan L; Thorpe, Andrew C; et al. (BJU international, 2021)
OBJECTIVE: To assess the differential response to neoadjuvant chemotherapy (NAC) in patients with urothelial carcinoma of the bladder (UCB) compared to upper tract urothelial carcioma (UTUC) treated with radical surgery. PATIENTS AND METHODS: Data from 1299 patients with UCB and 276 with UTUC were obtained from multicentric collaborations. The association of disease location (UCB vs UTUC) with pathological complete response (pCR, defined as a post-treatment pathological stage ypT0N0) and pathological objective response (pOR, defined as ypT0-Ta-Tis-T1N0) after NAC was evaluated using logistic regression analyses. The association with overall (OS) and cancer-specific survival (CSS) was evaluated using Cox regression analyses. RESULTS: A pCR was found in 250 (19.2%) patients with UCB and in 23 (8.3%) with UTUC (P < 0.01). A pOR was found in 523 (40.3%) patients with UCB and in 133 (48.2%) with UTUC (P = 0.02). On multivariable logistic regression analysis, patients with UTUC were less likely to have a pCR (odds ratio [OR] 0.45, 95% confidence interval [CI] 0.27-0.70; P < 0.01) and more likely to have a pOR (OR 1.57, 95% CI 1.89-2.08; P < 0.01). On univariable Cox regression analyses, UTUC was associated with better OS (hazard ratio [HR] 0.80, 95% CI 0.64-0.99, P = 0.04) and CSS (HR 0.63, 95% CI 0.49-0.83; P < 0.01). On multivariable Cox regression analyses, UTUC remained associated with CSS (HR 0.61, 95% CI 0.45-0.82; P < 0.01), but not with OS. CONCLUSIONS: Our present findings suggest that the benefit of NAC in UTUC is similar to that found in UCB. These data can be used as a benchmark to contextualise survival outcomes and plan future trial design with NAC in urothelial cancer.
Keywords: Female; protokoly protinádorové kombinované chemoterapie; lidé středního věku; cystektomie; Neoadjuvant Therapy; staging nádorů; mužské pohlaví; Methotrexate; Retrospective Studies; deoxycytidin; nádory močovodu; Kidney Neoplasms; cisplatina; retrospektivní studie; Humans; neoadjuvantní terapie; Urinary Bladder Neoplasms; Antineoplastic Combined Chemotherapy Protocols; methotrexát; Comparative Effectiveness Research; Deoxycytidine; Survival Rate; vinblastin; Vinblastine; Cystectomy; lidé; Doxorubicin; Middle Aged; míra přežití; Cisplatin; Neoplasm Staging; Proportional Hazards Models; Nephroureterectomy; senioři; srovnávací výzkum účinnosti; Ureteral Neoplasms; Treatment Outcome; ženské pohlaví; nádory ledvin; proporcionální rizikové modely; Aged; doxorubicin; Carcinoma, Transitional Cell; nádory močového měchýře; Male; výsledek terapie; karcinom z přechodných buněk; nefroureterektomie